Fresh and cultured mouse islets differ in their response to nutrient stimulation. Issue 8 (August 2020) - Morsi, Mai; Schulze, Torben; Früh, Eike; Brüning, Dennis; Panten, Uwe; Rustenbeck, Ingo
Abstract : Observing different kinetics of nutrient-induced insulin secretion in fresh and cultured islets under the same condition we compared parameters of stimulus secretion coupling in freshly isolated and 22-h-cultured NMRI mouse islets. Stimulation of fresh islets with 30 mM glucose after perifusion without nutrient gave a continuously ascending secretion rate. In 22-h-cultured islets the same protocol produced a brisk first phase followed by a moderately elevated plateau, a pattern regarded to be typical for mouse islets. This was also the response of cultured islets to the nutrient secretagogue alpha-ketoisocaproic acid, whereas the secretion of fresh islets increased similarly fast but remained strongly elevated. The responses of fresh and cultured islets to purely depolarizing stimuli (tolbutamide or KCl), however, were closely similar. Signs of apoptosis and necrosis were rare in both preparations. In cultured islets, the glucose-induced rise of the cytosolic Ca 2+ concentration started from a lower value and was larger as was the increase of the ATP/ADP ratio. The prestimulatory level of mitochondrial reducing equivalents, expressed as the NAD(P)H/FAD fluorescence ratio, was lower in cultured islets, but increased more strongly than in fresh islets. When culture conditions were modified by replacing RPMI with Krebs–Ringer medium and FCS with BSA, the amount of released insulin varied widely, but the kinetics always showed a predominant first phase. In conclusion, the secretion kinetics of fresh mouse islets is more responsive to variations of nutrient stimulation than cultured islets. The more uniform kinetics of the latter may be caused by a different use of endogenous metabolites.